A one-step four-bond-breaking reaction catalyzed by an electron - Davis, Daly; Vysotskiy, Victor P.; Sajeev, Yesodharan; Cederbaum, Lorenz S. (Angewandte Chemie. International edition, 2012)
Molecular demolition: Long-lived compound states involving a low-energy electron and a molecule generally involve the breaking of only one σ bond in the first elementary reaction step. Using high-level ab initio quantum-chemical methods, four-bond breaking in an elementary reaction step has been identified. Upon electron impact, a bicyclic molecule is shown to break four σ bonds in a concerted and essentially barrierless reaction step, producing three closed-shell neutral molecules.
Gesehen am 16.08.2018